Noise-Induced Hearing Loss in Gerbil: Round Window Assays of Synapse Loss - Jeffers, Penelope W. C.; Bourien, Jérôme; Diuba, Artem; Puel, Jean-Luc; Kujawa, Sharon G. (Frontiers in Cellular Neuroscience, 2021)
Previous work in animals with recovered hearing thresholds but permanent inner hair cell synapse loss after noise have suggested initial vulnerability of low spontaneous rate (SR) auditory nerve fibers (ANF). As these fibers have properties of response that facilitate robust sound coding in continuous noise backgrounds, their targeted loss would have important implications for function. To address the issue of relative ANF vulnerabilities after noise, we assessed cochlear physiologic and histologic consequences of temporary threshold shift-producing sound over-exposure in the gerbil, a species with well-characterized distributions of auditory neurons by SR category. The noise exposure targeted a cochlear region with distributed innervation (low-, medium- and high-SR neurons). It produced moderate elevations in outer hair cell-based distortion-product otoacoustic emission and whole nerve compound action potential thresholds in this region, with accompanying reductions in suprathreshold response amplitudes, quantified at 24 h. These parameters of response recovered well with post-exposure time. Chronic synapse loss was maximum in the frequency region initially targeted by the noise. Cochlear round window recorded mass potentials (spontaneous neural noise and sound-driven peri-stimulus time responses, PSTR) reflected parameters of the loss not detected by the conventional assays. Spontaneous activity was acutely reduced. Steady-state (PSTR plateau) activity was correlated with synapse loss in frequency regions with high concentrations of low-SR neurons, whereas the PSTR onset peak and spontaneous round window noise, both dominated by high-SR fiber activity, were relatively unaltered across frequency in chronic ears. Together, results suggest that acute targets of noise were of mixed SR subtypes, but chronic targets were predominantly low-SR neurons. PSTRs captured key properties of the auditory nerve response and vulnerability to injury that should yield important diagnostic information in hearing loss etiologies producing cochlear synaptic and neural loss.